Studying the Effect of New Didactic Tool on the Effectiveness of Educational Activity - Yurievna Glazkova, Irina; Mikhailovna Litvinova, Tatiana; Mikhailovna Kolomiets, Olga; Alexandrovna Smyslova, Olga (International Journal of Engineering and Technology, 2018)
This article presents the results of studies devoted to assessing the survival of students' knowledge, regardless of their basic training. The study was conducted based on two groups of specialists, recertified under the program "Pharmacy management and economics" at the Pharmacy Department of Sechenov First Moscow State Medical University. Some of the specialists of the experimental groups had been previously trained at the Pharmacy Department of Sechenov First Moscow State Medical University in 2012-2013 using a new developed didactic tool named "Activity Book". According to the results obtained, the skills acquired by the specialists trained using on "Activity Book" in 2012-2013, were characterized by higher "survivability".Â Â
Keywords: Didactic tool; Educational process; efficiency of educational activity.